Application Development To Manage Data And Information On Lettuce Production Companies - Totok Pujianto; Andre Prayudha; Irfan Ardiansah (Universitas Padjadjaran, 2017)
As a producer of lettuce plants, the company X (as a case object) needs to improve the information system more effectively and efficiently in order to support the increase of production. Therefore, it is necessary to build a management information system that provides information quickly and accurately. The implementation of this research using Waterfall Method. This research begins with the analysis of the needs of all users, then designing data flow diagrams, designing databases using SQL, entity relationship diagrams, normalization, the latter is the design of information structures including user interfaces. After that done programming activities using PHP programming language. This app is verified and validated. The information needs of the company are as follows: There are four parties as users of the information system; Information should be submitted and accessible as soon as possible; The manager can view the information of each division; To each division and vice versa; Managers can monitor the service level of marketing division and division of production; Each division can manage data; There needs to be model information about the agenda of each division. The app provides a shared menu for admins and users. Users are managers, marketing divisions, production divisions, and home packaging divisions. Each user has the same menu ie homepage, schedule, and reports. As for the manager plus menu monitoring. The final application prototype gives users satisfactory results. Each user is also given a menu to manage the database with features: inserting, searching, editing, and deleting data. The database comes with a dynamic and flexible user interface as a medium of data exchange and information between relevant divisions and media support in decision-making at the managerial level. Keywords— lettuce production, lettuce production database, production information system